Reconstruction of the Mudharabah Financing Agreement at Bank Syariah Indonesia - Siri, Rusli; Rahmi Rahmi (LP2M IAIN Palopo, 2024)
This research was motivated by the lack of maximum mudharabah financing due to the high risk experienced by Islamic banking. In addition, Islamic banks are extra careful in channeling mudharabah financing. This study aims to find out what the results of the reconstruction of mudharabah financing look like. Relating to rebuilding the mudharabah contract, the aims and practices align with what is determined in accordance with the basic principles of Islamic banking. Researchers use qualitative phenomenological approaches that are descriptive, analytical and inductive. This research seeks to explore data to find the basics of phenomena, reality and experience. This research uses documentary studies and studies of theories to explain and conclude the problems raised. This research is descriptive, which means it describes or describes a situation, symptoms, and events. In this case, to find out problems related to the status of Islamic banking as shahibul mal in the mudharabah contract that occurred at Bank Syariah Indonesia (BSI) Regional South Sulawesi. From various related information, from references that discuss mudharabah transactions and their application in Islamic banking that occur at Bank Syariah Indonesia (BSI) South Sulawesi Regional. This study concluded that the reconstruction carried out at BSI still did not go as expected. There are still many obstacles faced, including in determining profits. Meanwhile, the mudharabah contract applied at BSI is free from maysir, gharar, and usury elements—Mudharabah financing practices. The profit-sharing ratio given to mudharabah financing benefits both banks and customers. Profit sharing system where operational costs must reduce the profit earned by the fund manager and must also return the funds provided by shahibul maal therefore the profit obtained by the mudharib is by what is agreed. Various customers have felt this financing because customers who previously did not have the capital to do business with this financing customers can have capital provided by the BSI Regional South Sulawesi Bank. In practice, the distribution of profits between the two parties is based on a pre-agreed ratio. The ratio is the share of business profits for each party whose amount is determined based on the agreement. The partnership relationship in mudharabah financing is a collaboration between shahibul maal to provide funds. In contrast, the other party, mudharib, provides his mind, energy, and time to manage the cooperation business. The most important element in mudharabah financing cooperation is trust. This belief is mainly from shahibul maal to mudharib. Shahibulmaal should act as a supervisor to the mudharib to avoid business risks. The author advises BSI always to supervise customers when managing funds provided by banks in order to create transparency between the bank and customers. The bank should analyze the character and ability of prospective customers first before providing financing to customers to run a business and manage the funds provided by the bank, in order to minimize losses obtained by shahibul mall and can establish transparent cooperation and in accordance with Islamic economic principles